SCHOOL EDUCATION AND THE PLURILOCALITY OF TEACHING EVOKED BY CONTEMPORANEITY - Moraes Armesto, Leonardo; Paiva Gonçalves Bispo, Patrícia; Roberto Alonso, Thabata (Revista Gênero e Interdisciplinaridade, 2023)
Contemporaneity assumes, every day, the aggregation of a series of tools and mechanisms based on the possibilities of contributing to the training process of more active and knowledgeable citizens in their participation in the local context. This re-dimensioning consolidates itself in an increasingly faster social environment and full of deconstructions based on globalization that expands and links discussions, as well as the dynamics of plurality that problematize the forms, roots and aspects of the environment and of being. Nevertheless, it is part of this rhythm to bring to the school environment, whatever it may be, movements that are as typical as they are commonplace that transform the world every day and that forge new demands and requirements of the living being and inherent to its reality and to the narrowing influence that a locality exerts on the others that surround it. This makes the school a prosperous environment for the formation of ideas and generation of knowledge of the present time in contact with past history and the derived future.